The Effect Of External Debt On Economic Growth In Algeria. - ملاخسو بيلال (khazzartech الاقتصاد الصناعي, 2021)
The external debt problem is one of the most fatal problems facing the Arab states, as well as other developing countries, because of its serious impact on economic and social progress, as well as the fact that these countries suffer from declining domestic savings and export earnings, as well as increasing consumption rates, leading to a lack of domestic investment. Algeria, like many other underdeveloped countries, is significantly reliant on foreign loans to fund defaults and balance of payments issues. The major objectives of this paper, which employs traditional time series analysis, is to determine the link between foreign debt and macroeconomic indicators in Algeria from 1990 to 2010. The study’s key finding is that foreign debt has a detrimental influence on Algeria’s economic growth over the time period analyzed. For a variety of reasons, including domestic consumption and savings, investment, and the trade deficit.